Abrupt Discontinuation Versus Down-Titration of Vasopressin in Patients Recovering from Septic Shock. Issue 2 (February 2021) - Lam, Simon W.; Sacha, Gretchen L.; Duggal, Abhijit; Reddy, Anita J.; Bauer, Seth R.
ABSTRACT: Purpose: To compare patient outcomes based on management of arginine vasopressin (AVP) during the recovery phase of septic shock (abrupt vs. tapering discontinuation). Patients and Methods: Multicenter, retrospective cohort study of patients receiving AVP with concomitant norepinephrine for septic shock. Primary outcome measure was time to intensive care unit (ICU) discharge (from decision to titrate or stop AVP). Secondary outcomes included ICU and hospital mortality, and incidence of hypotension. Results: A total of 958 (73%) abrupt discontinuation and 360 (27%) down-titration patients were included. Patient characteristics and septic shock treatment courses were similar between groups. Median time to ICU discharge was similar between abrupt discontinuation (7.9 days, 95% CI 7.2–8.7 days) and tapered patients (7.3 days, 95% CI 6.3–9.3 days, P  = 0.60). After controlling for baseline discrepancies, down-titration was not an independent predictor of time to ICU discharge (HR = 0.99, 95% CI: 0.85–1.15, P  = 0.91). There was no difference in ICU mortality (21.8% vs. 18.0%, P  = 0.13) or hospital mortality (28.9% vs. 31.1%, P  = 0.44). Although incidence of hypotension was similar (39.7% vs. 41.7%, P  = 0.53), patients in the down-titration group more frequently required an escalation of AVP dose (5.7% vs. 11.1%, P  < 0.001). Median AVP duration was shorter in the abrupt discontinuation group (1.4 days [IQR: 0.6–2.6 days] vs. 1.8 days [IQR: 1.1–3.2 days], P  < 0.001). Conclusions: A difference in time to ICU discharge was not detected between abrupt AVP discontinuation and down-titration in patients recovering from septic shock. In patients recovering from septic shock, abrupt discontinuation of AVP appears to be safe and may lead to shortened AVP duration.